Harmonization of nucleic acid testing for Zika virus: development of the 1st World Health Organization International Standard. Issue 3 (23rd February 2017) - Baylis, Sally A.; Hanschmann, Kay‐Martin O.; Schnierle, Barbara S.; Trösemeier, Jan‐Hendrik; Blümel, Johannes
Abstract : BACKGROUND: With the ongoing public health emergency due to Zika virus (ZIKV), nucleic acid testing (NAT) is essential for clinical diagnosis and screening of blood donors. However, NAT for ZIKV has not been standardized, and this study was performed to establish a World Health Organization (WHO) International Standard (IS) for ZIKV RNA; WHO ISs have been used to improve detection and quantification of blood‐borne viruses. STUDY DESIGN AND METHODS: The candidate IS (cIS), code number 11468/16, was prepared by heat inactivation and lyophilization of a ZIKV strain isolated from a patient in French Polynesia in 2013. The cIS was evaluated together with other reference materials, including both Asian and African ZIKV lineages as well as a panel of clinical samples and in vitro–transcribed RNAs. The samples for evaluation were distributed to 24 laboratories from 11 countries. The assays used consisted of a mixture of in‐house developed and commercial assays (available or in development). RESULTS: The potencies of the standards were determined by quantitative and qualitative assays. In total, 37 sets of data were analyzed: 19 from quantitative assays and 18 from qualitative assays. Data demonstrated wide variations in reported potencies of the cIS and the other study samples. CONCLUSIONS: Assay variability was substantially reduced when ZIKV RNA concentrations from the biological reference materials and clinical samples were expressed relative to the cIS. Thus, the WHO has established 11468/16 as the 1 st IS for ZIKV RNA, with a unitage of 50, 000, 000 IU/mL.